2004
DOI: 10.3998/ark.5550190.0005.a10
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline derivatives from a marine-derived New Zealand Streptomycete

Abstract: Four new anthracycline derivatives, (7S*9R*10R*)-pyrromycin 1, (7R*9R*10R*)-pyrromycin 2, 1-hydroxyauramycin T 3, 1-hydroxysulfurmycin T 4, and the previously reported 1-hydroxyaclacinomycin B 5 were isolated from a New Zealand marine-derived Streptomycete. All five compounds were cytotoxic against the P388 murine leukaemia cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…99 A Streptomyces species from marine driftwood (West Coast, New Zealand) gave four new cytotoxic anthracycline derivatives (7S*,9R*,10R*)-pyrromycin 32, (7R*,9R*,10R*)-pyrromycin 33, 1-hydroxyauramycin T 34 and 1-hydroxysulfurmycin T 35. 100 An Actinomadura species from sea sediment (Jiaozhou Bay, China) contained the staurosporine analogue ZHD-0501 36, an inhibitor of the proliferation of a variety of murine and human cancer cell lines. 101 The phenolic bisabolane sesquiterpenoids (+)-curcutetraol 37 and (−)-curcutriolamide 38 were isolated from a co-culture of unidentified bacterium and fungus separated from marine sediment (Bahamas).…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…99 A Streptomyces species from marine driftwood (West Coast, New Zealand) gave four new cytotoxic anthracycline derivatives (7S*,9R*,10R*)-pyrromycin 32, (7R*,9R*,10R*)-pyrromycin 33, 1-hydroxyauramycin T 34 and 1-hydroxysulfurmycin T 35. 100 An Actinomadura species from sea sediment (Jiaozhou Bay, China) contained the staurosporine analogue ZHD-0501 36, an inhibitor of the proliferation of a variety of murine and human cancer cell lines. 101 The phenolic bisabolane sesquiterpenoids (+)-curcutetraol 37 and (−)-curcutriolamide 38 were isolated from a co-culture of unidentified bacterium and fungus separated from marine sediment (Bahamas).…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…10). 176 In addition, anthracyclines such as mutactimycin PR (49), 185 demethyl mutactimycin (50), 186 komodoquinone A (51) 187 and andicoquinones A-D (52-55) 183 have been isolated (Fig. 10).…”
Section: Reviewmentioning
confidence: 99%
“…9). 176 G0041-3c ( 36 ) contains an additional carbohydrate at C10, 177 while obelmycin H ( 37 ) and its congener A262-6 ( 38 ) are glycosylated only at this position. 178 In turn, histomodulin ( 39 ) is a rhodomycin derivative containing a glucopyranuronosyl unit at C4.…”
Section: Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…(CANU Fox 21-2-6) isolated from the mouth of the Fox River. The bioactivity evaluation showed that all four compounds displayed considerable cytotoxicity against P388 cultured cells, with 50% infectious dose (ID 50 ) values ranging from 0.4 to 0.06 µg/ml (Phipps et al, 2004). Two anthracyclines, 5-iminoaranciamycin (10) and tetracenoquinocin (11), were isolated from a culture broth of Streptomyces sp.…”
Section: Marine-sourced Bacteria Derived Natural Productsmentioning
confidence: 99%